Reduction of TSS, COD, Oil and Fat in Palm Oil Mill Waste Using Dissolved Air Flotation Method - Florida Agustina Sinaga; M. Turmuzi Lubis; Amir Husin (Fakultas Teknik, 2022)
This study aims to determine the effect of variations in pressure and contact time of wastewater with air to decrease the parameters of TSS, COD, and oils and fats contained in palm oil wastewater. This study uses a series of Dissolved Air Flotation (DAF) process units with the addition of Poly Aluminum Chloride (PAC) coagulant. This research begins with the manufacture of a series of DAF tanks and flotation tanks. Waste flow is carried out in batches and the air is flowed upflow through the bottom hole of the DAF tank. The pressure variables used in decreasing the parameters of TSS, COD, and oil and fat are absolute 2; absolute 2.5; and absolute 3 atm. The contact time variables for decreasing TSS, COD, and oil and fat parameters were 15, 30, 45, 60, and 75 minutes. The results showed a decrease in each of the tested parameters. The effective pressure to reduce the value of the TSS parameter is the absolute pressure of 3 atm and the absolute pressure of oil and grease is 2.5 atm. While the effective pressure to reduce the value of the COD parameter is an absolute pressure of 3 atm. The best contact time between air and wastewater to set aside the values of the TSS, COD, and oil-fat parameters was 75 minutes.